What is radical about the ordinary? - Hauerwas, Stanley (Scottish journal of theology, 2011)
‘Radical Ordinary’ seemed like a good idea. The ‘ordinary’ is just, well, it is just so ordinary. No one is particularly attracted to the ‘ordinary’. But our lives are sustained by the ‘ordinary’. So maybe one of the ways to remind us of the significance of the ordinary is to qualify the ordinary by the word ‘radical’. A clever strategy that may, given Bowlin's response to the book Coles and I wrote, be far too clever.